Traffic-related air pollution significantly aggravates the detrimental effect of infections on the risk of Alzheimer’s disease and other dementias, especially in non-carriers of APOE4 - Popov, Vladimir A.; Ukraintseva, Svetlana; Duan, Hongzhe; Yashkin, Arseniy; Kravchenko, Julia; Akushevich, Igor; Whitson, Heather; Arbeev, Konstantin G.; Yashin, Anatoliy I. (Frontiers in Dementia, 2026)
Alzheimer’s disease (AD) is a complex neurodegenerative disorder influenced by various factors, including genetic and exposure-related. Certain combinations of these factors may promote AD more substantially than others. APOE4 is the strongest genetic risk factor for AD. Traffic-related air pollution (TRAP) and infections are important exposure-related AD risk factors. Here we investigated how the interplay between a history of infections and chronically high exposure to TRAP (highTRAP) impacts the subsequent risk of AD and other dementias (AD+) in carriers and non-carriers of APOE4 in UK Biobank (UKB) participants aged 60–75 years. HighTRAP was approximated by the proximity (50 meters or less) of a participant’s primary residence to a major road. Chi-square, Wilson score interval, Wald interval, Wald risk ratio, Welch tests, and regression were used to examine statistical significance. We found that UKB participants with a history of various infections (by ICD-10 codes), but without highTRAP, had a 54% increase in AD+ risk. HighTRAP alone did not significantly influence AD+ risk. Individuals with both a history of infections and highTRAP had a 164% higher risk of AD+ compared to those without either factor. That risk was much higher (349%) in non-carriers of APOE4 but became non-significant in APOE4 carriers. We conclude that avoiding high exposure to TRAP may significantly reduce the risk of AD in non-carriers of APOE4 with a history of infections but not in carriers. One potential explanation could be that APOE4 is a stronger AD risk factor, whose AD-promoting effects may outweigh those of other risk factors.